CTNI-02. TBCRC049: A PHASE II STUDY TO ASSESS THE SAFETY AND EFFICACY OF THE COMBINATION OF TUCATINIB, TRASTUZUMAB AND CAPECITABINE FOR THE TREATMENT OF LEPTOMENINGEAL METASTASIS IN HER2 POSITIVE BR1AST CANCER. (9th November 2020) - Murthy, Rashmi; O'Brien, Barbara; Berry, Donald; Navin, Nicholas; Johnson, Jason; Gule-Monroe, Maria; Leone, Jose; Specht, Jennifer; Melisko, Michelle; Morikawa, Aki; Storniolo, Anna; Brufsky, Adam; et al.
Abstract: Treatment options for patients with leptomeningeal metastasis (LM) from HER2-positive breast cancer (HER2+ BC) are limited and prognosis is poor. Tucatinib is an oral, potent, HER2 specific tyrosine kinase inhibitor with good tolerability and combinatory anti-tumor activity, including partial responses in heavily treated patients and those with brain metastases (BM). This is a phase 2 single-arm study to evaluate the efficacy of tucatinib, trastuzumab and capecitabine in HER2+ BC with newly-diagnosed LM. CNS disease will be evaluated at screening and every 6 weeks by neuroaxis MRI, CSF cytology, and neurological assessments per RANO-LMD (adapted) and RANO-BM criteria. Extra-CNS disease will be evaluated at screening and every 12 weeks by CT scan per RECIST criteria. All patients will be followed for survival. Symptom burden and quality of life assessments, as well as correlative blood and CSF samples, will be collected. Eligible patients include adults with HER2+ BC, KPS > 50, and newly-diagnosed, untreated LM (defined as positive CSF cytology and/or radiographic evidence of LM, plus clinical signs/symptoms). Patients with treated or concurrent/new BM are allowed. Patients treated with capecitabine within the last 12 months are excluded. This study has a Gehan-like design with an interim futility analysis and overall intent to estimate OS. For the interim analysis, success is defined as CNS PFS for 12 weeks. Enrollment will end if fewer than two successes are observed in the first 15 patients. Secondary endpoints include safety, CNS PFS at 12 weeks, RR in CNS and extra-CNS, and symptom burden/quality of life. The regimen will be considered worthy of future study if the median OS is > 4.4 months. Fourteen of 30 patients have accrued thus far. The study is active at multiple Translational Breast Cancer Research Consortium sites around the country.